2011
DOI: 10.2174/187152611796504782
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Mechanical Ventilation to Prevent ICU-Acquired Infection

Abstract: Several forms of supportive techniques for respiration in intensive care units (ICU) are currently available. The most widely used is invasive mechanical ventilation through the use of an endotracheal tube (ETT). ETTs are proved to be important contributors to the pathogenesis and development of ventilator-acquired pneumonia (VAP) as artificial airways interfere with a number of respiratory tract defence mechanisms and facilitate bacterial colonisation of the tracheobronchial tree. The occurrence of VAP is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…A statistic analysis on the data on such unique individuals indicated that the patients in mechanical ventilation experienced moderate and higher level of intensive care experience, which was consistent with the previous results of researches with westerners as the research objects [16][17]. Baudry has reported cases mental disturbance arising from ICU care and proposed the concept of intensive care syndrome [18]. Some scholars have proposed that the ICU syndrome is a individual mode generated by the patient in ICU.…”
Section: Discussionsupporting
confidence: 80%
“…A statistic analysis on the data on such unique individuals indicated that the patients in mechanical ventilation experienced moderate and higher level of intensive care experience, which was consistent with the previous results of researches with westerners as the research objects [16][17]. Baudry has reported cases mental disturbance arising from ICU care and proposed the concept of intensive care syndrome [18]. Some scholars have proposed that the ICU syndrome is a individual mode generated by the patient in ICU.…”
Section: Discussionsupporting
confidence: 80%
“…The use of ETT is also a cause of microbial colonization due to the formation of biofilms. ETT was considered as the significant cause of development of ventilator associated pneumonia 23. A study conducted to detect the correlation of infections with various invasive procedures in different units of hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Invasive mechanical ventilation has a number of drawbacks and side effects. It requires deep sedation [9,10], exposes to the risk of ventilatorassociated pneumonia, extends hospital stay [11e13], and the child can end up ventilator dependent [14,15]. Therefore in many centers invasive mechanical ventilation is instituted only when there is reasonable expectancy that the patient is weaned off the ventilator.…”
Section: Introductionmentioning
confidence: 99%